2013
DOI: 10.1002/anie.201209229
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Exfoliated MoS2 as Near‐Infrared Photothermal Agents

Abstract: Two‐dimensional bio‐dynamite: Chemically exfoliated MoS2 (ceMoS2), a water‐dispersible sheet‐like material, is an efficient near‐infrared (NIR) photothermal transducer. The superior bio‐supramolecular properties of ceMoS2 and the ability of this material to destroy biomolecular targets through near‐infrared (NIR) photothermal transduction were studied (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
402
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 608 publications
(413 citation statements)
references
References 51 publications
10
402
0
1
Order By: Relevance
“…In a recent work, Chou et al for the fi rst time demonstrated the possibility of using as-made MoS 2 nanosheets as a new NIR absorbing agent for in vitro-photothermal-killing of cancer cells in vitro at the cell culture level. [ 19 ] In another latest report, Li et al demonstrated in vivo-photothermal-ablation of tumors by local injection of Bi 2 Se 3 nanosheets directly into tumors. [ 20 ] The in vivo applications of TMDCs, particularly with well-controlled surface functionalization to achieve therapeutic effect in animals after systemic administration, however, remain to be explored.…”
Section: Doi: 101002/adma201304497mentioning
confidence: 99%
“…In a recent work, Chou et al for the fi rst time demonstrated the possibility of using as-made MoS 2 nanosheets as a new NIR absorbing agent for in vitro-photothermal-killing of cancer cells in vitro at the cell culture level. [ 19 ] In another latest report, Li et al demonstrated in vivo-photothermal-ablation of tumors by local injection of Bi 2 Se 3 nanosheets directly into tumors. [ 20 ] The in vivo applications of TMDCs, particularly with well-controlled surface functionalization to achieve therapeutic effect in animals after systemic administration, however, remain to be explored.…”
Section: Doi: 101002/adma201304497mentioning
confidence: 99%
“…Especially, single-layer MoS 2 nanosheets show desirable characteristics of NIR absorption and high light-to-heat conversion efficiency, indicating that they can act as photothermal agent for PTT [112]. Importantly, MoS 2 is considered to be biocompatible because Mo element is found to be an essential traceable element for certain types of enzymes in cells and S element is abundant in biological systems, from the viewpoint of chemical composition of TMDCs.…”
Section: Mos 2 Nanosheetsmentioning
confidence: 99%
“…In addition, another attractive feature lies inthe fact that their electronic structures and some other properties are highly tunable through chemical modification, doping and different kinds of hybridization, allowing one to tune their electronic properties in a desired manner at a highly controllable level (Huang et al 2013c;Rong et al 2015b;Wei et al 2015). Similar with graphene, some of the graphene analogues possess high photothermal conversion efficiency and have been explored for photothermal/photodynamic therapy (Chou et al 2013).…”
Section: Introductionmentioning
confidence: 99%